ANALISIS KESELAMATAN JALAN DENGAN PENDEKATAN AUDIT KESELAMATAN JALAN PADA JALAN LOKAL DI KOTA TEGAL - Irsyad, Bani; Putri, Raudina Rilawani; Hadi, Suprapto; Varadinta, Salsabilla; Nazzaya, Muhammad Rifqi (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2024)
Jalan Sultan Hasanudin – KH. Abdul Ghoni, which is located in Tegal City, Central Java, is a road with a secondary local function which is an alternative way to get to primary roads. By being an alternative road, this road section must meet adequate road safety standards. To improve traffic safety, it is necessary to carry out a road safety audit. This research aims to see the level of road safety in Tegal City, specifically on the Jalan Sultan Hasanudin - Jalan KH section. Abdul Ghoni. The method used in this research is descriptive quantitative obtained from the Hawkeye survey and processed using the Hawkeye processing toolkit software to analyze the data. The research results show that the Sultan Hasanudin – KH. Abdul Ghoni, in the aspect of road equipment facilities, there are 7 road equipment facilities in a damaged condition, in the aspect of the level of road unevenness in the medium category it has a percentage of 45% of the total length of the section, and for the aspect of the transverse slope on the Jl. Sultan Hasanuddin – KH. Abdul Ghoni has not met the standard for the transverse slope of asphalt pavement. Improved safety on the Jl. Sultan Hasanudin carried out further handling and improvements to road equipment and road pavement facilities, so that the Jl. Sultan Hasanuddin – KH. Abdul Ghoni does not have the potential to cause traffic accidents due to deficiencies in road infrastructure or dangerous road conditions.